Dental story sticker media as an effort to increase dental and oral health knowledge of elementary school students - Aulia Salsabila Putri; Tri Widyastuti; Rr. Megananda Hiranya Putri; Yonan Heriyanto (Center of Excellent (Pusat Unggulan Iptek), 2023)
Introduction: The results of the National Basic Health Research 2018, as many as 57.6% of Indonesia's population has oral dental problems and only 10.2% do Get the services of a dentist. The health education given to the community, including for children, is usually implemented using various preventive and promotional measures. Giving Education can be one way to increase knowledge prevent dental and oral health problems. Media Dental Story Sticker is a tool that can be used for education dental health. Dental Story Sticker is a media for dental and oral health in its presentation using stickers that can be removed and installed back and apply the storytelling method as an extension method where the instructor talks about the counseling material related to dental and oral health. Purpose: The purpose of this study was to analyze the effect of dental health education using dental media story stickers on dental health knowledge of second grade elementary school students. Methods: Using the analytic research method with a pre-experimental research design with a one group pretest-posttest design. Samples were taken using total sampling with a total of 34 people. Research analysis used the Wilcoxon Results test: The results showed that children's knowledge of maintaining oral hygiene before Dental Health Education was carried out using dental story sticker media, namely 22 children (64.7%), while after Dental Health Education was carried out using dental story sticker media, all respondents (100%) have knowledge in a good category with a p value = 0.000 (p <0.05). This means that there is a dental influence health education using dental story sticker media. Conclusion: It can be concluded that dental story sticker media as a dental health education media has an influence on the level of dental and oral health knowledge.